2013
DOI: 10.1186/1471-2458-13-1161
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity prevalence in the general population: the role of obesity in chronic disease clustering

Abstract: BackgroundThe role of obesity in the prevalence and clustering of multimorbidity, the occurrence of two or more chronic conditions, is understudied. We estimated the prevalence of multimorbidity by obesity status, and the interaction of obesity with other predictors of multimorbidity.MethodsData from adult respondents (18 years and over) to the Health Quality Council of Alberta 2012 Patient Experience Survey were analyzed. Multivariable regression models were fitted to test for associations.ResultsThe survey s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
108
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 21 publications
14
108
2
2
Order By: Relevance
“…First, although multimorbidity was higher in the older population (65+ years), 2.2% of Canadians aged 20 to 65 years reported 3 or more coexisting chronic conditions, and 8.8% reported 2 or more coexisting chronic conditions, in keeping with previous Canadian studies. 11 Second, the association of risk factors and multimorbidity increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although multimorbidity was higher in the older population (65+ years), 2.2% of Canadians aged 20 to 65 years reported 3 or more coexisting chronic conditions, and 8.8% reported 2 or more coexisting chronic conditions, in keeping with previous Canadian studies. 11 Second, the association of risk factors and multimorbidity increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the choice of conditions can influence prevalence estimates. For example, Agborsangaya et al 11 found that 36% of Albertans had two or more chronic conditions, but their definition included obesity, which itself had a prevalence of…”
Section: Introductionmentioning
confidence: 99%
“…Another common multi-morbid condition is obesity that is known for its association with both MS and CVD, but also for less a number of chronic diseases with less obvious links to excessive adiposity, including arthritis, asthma and cancer [5, 6]. Recent study showed that obesity was associated with more than double the odds of multi-morbidity as compared to non-obese cohort [7].…”
Section: Introductionmentioning
confidence: 99%
“…The avoidable risk factors for the healthy years lost due to rising disease burden include high BMI and physical inactivity according to the Global Burden of Disease report of USA, [14]. Obese people had two fold higher chances of having multi-morbidities [1]. In many studies.…”
Section: Introductionmentioning
confidence: 99%